Research Themes for Tourism - Robinson, Peter (CABI, 2014)
Tourism is a central feature of modern society and af ects every part of the world and every person in the world. Within Western societies, it is hard to imagine a world without holidays and opportunities for travelling to new places for new experiences. There are still a number of people for whom this remains a distant possibility, and others who may never holiday, but perform a part of the tourist experience through their cultural heritage. Within destinations, whether in the developed or developing world, new attractions are built or existing ones adapted. Accommodation, entertainment, transport and other ancillary services are central to the experiences. Tourism’s essence is the physical movement of people. Ever since beginning of humanity, people have travelled for various reasons. During ancient times, the main reason for travelling was war and the territorial expansion of countries through conquest. This continued throughout the Middle Ages with the discovery and exploration of America and later Australasia, although during these times religion was a major motivator as worshippers set out on pilgrimages. Until the 1840s tourism remained a pursuit of the rich who were able to travel for months at a time, exploring Europe and the edges of Africa and Asia to learn about cultures and bring back new ideas for architecture and society. Many treasures were traded and researched through these travels, expeditions that became known as ‘the Grand Tour’, resulting in collections in national museums of treasures brought back from abroad for cultural enlightenment at home. Within Europe, the Grand Tour had a major inﬂ uence on travelling. After the rich and aristocratic had led the way, the rest of society was able to follow – the advance of steam railways, advent of paid holidays and emergence of seaside resorts resulted in the working classes travelling in masses.